Retrovirus-mediated transduction of adult hepatocytes. - Wilson, J M (1988)
Retrovirus-mediated gene transfer was used to develop a method for introducing genes into primary cultures of adult rat hepatocytes. Subconfluent monolayers of hepatocytes, cultured in hormonally defined media on different matrix substrata, were infected with helper-free stocks of a replication-defective retrovirus that constitutively expresses high levels of beta-galactosidase. Retrovirus-mediated transduction was measured by two methods: (i) an in situ cytochemical stain that specifically detects the expression of viral expressed beta-galactosidase, and (ii) Southern blot analysis, which measures the relative copy number of integrated provirus. Maximal transduction efficiency of approximately equal to 25% was achieved when the cells were infected after 3 days in culture; matrix had little effect on transduction efficiency. Enzyme cytochemical (catalase and glucose 6-phosphatase) and peroxidase immunocytochemical (asialoglycoprotein and UDP-glucuronosyltransferase) analyses of the cultures indicated that greater than 95% of cells were hepatocytes. The demonstration of hepatocyte-specific organelles in cells expressing the viral-directed beta-galactosidase provided unambiguous evidence for the transduction of hepatocytes. These methods should be useful in the development of liver-directed somatic gene therapy and in the study of liver-specific gene regulation.